A preliminary study on the fuzzy analytical hierarchy process (FAHP) for the prioritization of flash flood risk index in development projects - Mohammad Syamsyul Hairi, Saad; Mohamad Idris, Ali; Putri Zulaiha, Razi; Bawono, Adi Setiabudi; Noram Irwan, Ramli (Institute of Physics, 2025)
Flash floods are a significant threat to urban development in Malaysia, often reported to be related to construction activities. The construction activity is one of the stages of any development project. This research aims to develop a comprehensive framework using the Fuzzy Analytical Hierarchy Process (FAHP) for prioritizing flash flood risk index in new development projects. The methodology involves constructing a hierarchical model of flash flood risk vulnerability factors, conducting expert assessments using fuzzy logic to handle imprecise and uncertain information, and converting qualitative data into quantitative ratings. Six experts from academia, industry, and government were involved in assessing factors influencing the flash flood vulnerability during development projects' pre-construction and construction phases. Findings reveal that construction phases and best management practices (BMPs) are critical in mitigating flash flood risks. The FAHP framework effectively prioritizes the flash flood risk index, offering a scientifically validated and flexible approach to decision-making. This study contributes to the field by providing a robust method for integrating expert judgments and handling uncertainties in flash flood risk assessment. This research demonstrates the effectiveness of FAHP in improving flood risk management for new development projects in Malaysia. This study enhances decision-making by addressing the identified gaps, ensuring more resilient and sustainable infrastructure development. Future research should focus on refining the FAHP model and developing user-friendly tools for wider urban planning and construction adoption.